2014
DOI: 10.1016/j.antiviral.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

MEK/ERK activation plays a decisive role in yellow fever virus replication: Implication as an antiviral therapeutic target

Abstract: Exploiting the inhibition of host signaling pathways aiming for discovery of potential antiflaviviral compounds is clearly a beneficial strategy for the control of life-threatening diseases caused by flaviviruses. Here we describe the antiviral activity of the MEK1/2 inhibitor U0126 against Yellow fever virus 17D vaccine strain (YFV-17D). Infection of VERO cells with YFV-17D stimulates ERK1/2 phosphorylation early during infection. Pharmacological inhibition of MEK1/2 through U0126 treatment of VERO cells bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 49 publications
1
32
1
1
Order By: Relevance
“…Dengue virus serotype 2 (DENV-2) participates in liver inflammation by inducing the expression of various chemokines through activating all three MAPK pathways (52). YFV infection induces ERK1/2 activation, and treatment with U0126 reduces the level of YFV replication by 99% (38). A similar inhibitory effect of the ERK inhibitor was also observed in infections with dengue virus (DENV-2 and -3) and St. Louis encephalitis virus (SLEV) (38).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Dengue virus serotype 2 (DENV-2) participates in liver inflammation by inducing the expression of various chemokines through activating all three MAPK pathways (52). YFV infection induces ERK1/2 activation, and treatment with U0126 reduces the level of YFV replication by 99% (38). A similar inhibitory effect of the ERK inhibitor was also observed in infections with dengue virus (DENV-2 and -3) and St. Louis encephalitis virus (SLEV) (38).…”
Section: Discussionmentioning
confidence: 61%
“…YFV infection induces ERK1/2 activation, and treatment with U0126 reduces the level of YFV replication by 99% (38). A similar inhibitory effect of the ERK inhibitor was also observed in infections with dengue virus (DENV-2 and -3) and St. Louis encephalitis virus (SLEV) (38). AMPK, an intracellular energy sensor, plays a pivotal role in cellular metabolism, particularly in lipid and glucose metabolism (53).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In turn, the MEK1/2 [mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase (ERK) kinase]/ERK1/2 signaling pathway prevents the LKB1-AMPK signaling [61], thus the stimulation of the MEK/ERK pathway in DENV infected cells could explain the depletion of AMPK phosphorylation. Several authors demonstrated that DENV [62] and others flaviviruses including Hepatitis C Virus (HCV) [63], West Nile fever virus (WNV) [64], Japanese encephalitis virus (JEV) [65] and yellow fever virus (YFV) [66] cause the turn on of the MEK/ERK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular signalling cascades are key to these regulatory events because they can be rapidly activated or deactivated and not only are vital in controlling important cellular processes but also modulate viral propagation. Flaviviruses, including yellow fever virus, Saint Louis encephalitis virus, and dengue virus, as well depend on Raf/MEK/ERK-mediated signalling for efficient replication (Albarnaz et al, 2014). Several cascades have been described to be involved in viral replication, such as the PI3K/Akt cascade, MAPK cascade, PKC/PKR cascade, and NF-κB signalling module (reviewed in Gaur, Munjal, & Lal, 2011;reviewed in Diehl & Schaal, 2013 Pleschka et al, 2001;Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%